Cardiovascular Magnetic Resonance for the Evaluation of Arrhythmogenic Substrates in Patients with Systemic Autoimmunity: An Update - George Markousis-Mavrogenis; Petros P. Sfikakis; Anne Hui Sze Kwong; Alessia Pepe; Marco Matucci-Cerinic; George D. Kitas; Sophie I. Mavrogeni (Reviews in Cardiovascular Medicine, 2023)
Patients with systemic autoimmunity due to autoimmune rheumatic diseases (ARDs) or sarcoidosis frequently present with systemic manifestations including cardiac involvement. Cardiac rhythm disturbances and specifically ventricular arrhythmias (VAs) may affect the prognosis of these patients. Cardiovascular magnetic resonance imaging (CMR) is a non-invasive imaging modality that can provide valuable diagnostic and prognostic information in patients with ARDs or systemic autoimmunity in general. In this narrative review, we briefly present the underlying pathophysiologic mechanisms contributing to arrhythmogenicity in patients with systemic autoimmunity. Furthermore, we discuss recent advances underlying the role and value of CMR for use in the detection and risk stratification of arrhythmogenic substrates in patients with systemic autoimmunity and VAs.